Do wolframin, P-glycoprotein, and GRP78/BiP cooperate to alter the response of L1210 cells to endoplasmic reticulum stress or drug sensitivity? - Simona Kurekova; Lucia Pavlikova; Mario Seres; Viera Bohacova; Jana Spaldova; Albert Breier; Zdena Sulova (Cancer Cell International)
Abstract In previous research, we revealed that murine leukemia cells L1210 with induced expression of P-glycoprotein (P-gp, a membrane drug transporter, product of the Abcb1 gene) are better able to withstand endoplasmic reticulum (ER) stress (ERS) than their P-gp negative counterparts. This was associated with increased GRP78/BiP expression and modulation of the expression of several other proteins active in the cellular response to ERS (like CHOP, spliced XBP1, 50-kDa ATF6 protein fragment and others) in P-gp positive cells. Wolframin is an ER transmembrane protein, product of the WFS1 gene whose mutations are associated with Wolfram syndrome. However, this protein is frequently overexpressed in cells undergoing ERS and its expression may accompany changes in the above ERS markers. Therefore, our aim in this work was to investigate wolframin expression in P-gp-negative and P-gp-positive murine leukemia L1210 cells in relation to ERS related proteins in normal or ERS condition. We induced ERS in cells either by blocking N-glycosylation in the ER with tunicamycin or by blocking ER Ca2+-ATPase activity with thapsigargin, as known ER stressors. The results of this paper demonstrated increased wolframin expression in P-gp positive cells compared to P-gp negative cells. Immunoprecipitation experiments revealed the formation of complexes between wolframin and ERS related proteins (PERK, ATF6 and GRP78/BiP), the amount of which varied depending on the presence of the above ER stressors. Graphical Abstract